Advancing the work family enrichment theory by including the self domain - Yang, Zhao (2019)
This thesis examines the moderating effect of individual differences in personal culture orientations, especially interdependence and prudence dimension, on work to family affective enrichment in China context. This thesis highlights that individual differences play an essential and coherent role in understanding a work family enrichment process. This thesis adopted a quantitative approach to investigate 551 middle - and high-income Chinese employees. The self-administered questionnaire based survey was conducted to collect data during October - December 2017 in Beijing, China. In total, respondents included 326 part-time MBA students and 225 full-time employees. Data was analyzed by Structure Equation Model technique using LISREL 10.0 software. Multiple group analysis was used to test the moderating effect of interdependence and prudence on work to family affective enrichment. The results showed that individuals with low levels of interdependence and prudence orientations toward work positively responded to the family support and reported a higher level of work to family affective enrichment. This thesis also revealed that family support was essential in predicting family to work enrichment. Supervisor support had the strongest effect on work to family behavior enrichment, and absence support had the strongest effect on work to family affective enrichment. This thesis extends the culture sensitive theory of work-family interface from a national level to an individual level by introducing the personal cultural orientations in the work family enrichment literature.